Cardioembolic Stroke: Mechanisms and Therapeutics - Sacchetti, Daniel C.; Furie, Karen L.; Yaghi, Shadi (Seminars in Neurology, 2017)
Cardioembolic stroke accounts for nearly 30% of all known stroke mechanisms. This percentage may be underestimated, however, when considering the large proportion of cryptogenic strokes that likely have a covert cardiac source. Although it is well known that cardioembolic stroke can occur in the setting of atrial fibrillation, other mechanisms such as a systolic heart failure, patent foramen ovale, valvular dysfunction, and aortic arch atheroma are commonly encountered in daily practice. The authors provide an overview on the epidemiology, pathogenesis, diagnostic evaluation, and secondary prevention treatment strategies for cardioembolic stroke.
Keywords: stroke; transient ischemic attack; cardioembolism; stroke prevention; patent foramen ovale